2020
DOI: 10.1136/neurintsurg-2020-016140
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for diagnostic cerebral angiograms in the elderly: a comparative observational study

Abstract: BackgroundThe transradial approach (TRA) reduces mortality, morbidity, access site complications, hospital cost, and length of stay while maximizing patient satisfaction. We aimed to assess the technical success and safety of TRA for elderly patients (aged ≥75 years).MethodsA retrospective chart review and comparative analysis was performed for elderly patients undergoing a diagnostic cerebral angiogram performed via TRA versus transfemoral approach (TFA). Also, a second comparative analysis was performed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…We chose to use the 10-item Patient-Reported Outcomes measurement Information System GHS because it is a well-known valid and reliable scale used in assessing and tracking the impact of healthcare interventions in health and functional disability over time. This novel finding from our 30-day postprocedural PRO adds to previous literature [1][2][3][4][5] that only reported immediate QOL outcome with the TRA approach during the postoperative phase. These studies demonstrated a higher satisfaction rate with the radial approach mainly because of a shorter recovery time likely related to postprocedural comfort and reduced hospital stay.…”
Section: Discussionsupporting
confidence: 65%
“…We chose to use the 10-item Patient-Reported Outcomes measurement Information System GHS because it is a well-known valid and reliable scale used in assessing and tracking the impact of healthcare interventions in health and functional disability over time. This novel finding from our 30-day postprocedural PRO adds to previous literature [1][2][3][4][5] that only reported immediate QOL outcome with the TRA approach during the postoperative phase. These studies demonstrated a higher satisfaction rate with the radial approach mainly because of a shorter recovery time likely related to postprocedural comfort and reduced hospital stay.…”
Section: Discussionsupporting
confidence: 65%
“…In a comparative analysis of patients aged >75 years, Sweid et al noticed that radiation exposure per vessel was significantly lower in the elderly TRA group than the elderly TFA group (p=0.001). 32 However, there were no significant differences between TRA and TFA groups for contrast dose, fluoroscopy time, procedure duration, crossover rate, or access site complications. A second comparison (TRA in elderly versus TRA in the young) showed no significant differences for contrast dose, radiation exposure, procedure duration, access site complication or cross-over rate.…”
Section: Discussionmentioning
confidence: 79%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]33,34 This prompted numerous other studies which were directed explicitly towards cerebral angiography and neuro-intervention, albeit on a smaller scale. 8,29,32 In the study by Osbun et al intraoperative cerebral angiography from a TRA was technically feasible for a variety of cerebrovascular pathologies without any access site complications or postoperative hand ischemia. 8 Moreover, they demonstrated its applicability in different patient positions and improved the work-flow ergonomics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations